Elective nodal ultra hypofractionated radiation for prostate cancer: Safety and efficacy from four prospective clinical trials. (October 2021) - Glicksman, Rachel M.; Liu, Stanley K.; Cheung, Patrick; Vesprini, Danny; Chu, William; Chung, Hans T.; Morton, Gerard; Deabreu, Andrea; Davidson, Melanie; Ravi, Ananth; Musunuru, Hima Bindu; Helou, Joelle; et al.
Highlights: Ultra-hypofractionated elective nodal RT was studied in 4 prospective trials. The incidence of grade 3+ acute or late GI or GU toxicity was low. Bowel and sexual quality of life worsened for 1 year post treatment. Oncologic outcomes were very favorable, however longer follow-up is needed. This is the largest prospective series of ultra-hypofractionated elective nodal RT. Abstract: Background and purpose: The role of elective nodal irradiation (ENI) in localized prostate cancer (PCa) is controversial. With increasing use of SBRT to the prostate, data is needed regarding the safety and efficacy of ENI using ultra-hypofractionated radiation (UHRT). Materials and methods: Between 2013–2020, 4 prospective clinical trials of intermediate or high-risk PCa receiving dose-escalated RT to the prostate (via HDR brachytherapy or SBRT boost) and ENI using UHRT (25 Gy in 5 weekly fractions) were conducted. Primary endpoints included acute genitourinary and gastrointestinal toxicities (CTCAE v3.0/4.0), and secondary endpoints included late genitourinary and gastrointestinal toxicities, patient-reported quality of life (EPIC) and biochemical failure (Phoenix definition). Results: One-hundred sixty-five patients were enrolled, of whom 98 (59%) had high-risk disease. ADT was used in 141 (85%). Median follow-up was 38 months (IQR 10–63). The worst acute genitourinary and gastrointestinal toxicities respectively were 48% and 7.5% for grade 2, and 2.7% and 0% for grade 3. Cumulative incidence of late grade 2+ genitourinary and gastrointestinal toxicities at 36 months were 58% and 11.3% and for late grade 3+ toxicities were 1% and 0%, respectively. No grade 4+ acute or late toxicities were observed. Bowel and sexual toxicity significantly worsened up to 1-year compared to baseline. Over time, urinary ( p  < 0.0001), bowel ( p  = 0.0018) and sexual ( p  < 0.0001) scores significantly improved. The 3-year biochemical recurrence-free survival was 98%. Conclusion: ENI using UHRT is associated with low incidence of grade 3+ toxicity, while grade 1–2 acute genitourinary and gastrointestinal toxicity is common. Randomized phase 3 trials are needed.